Descriptive and injunctive network norms associated with nonmedical use of prescription drugs among homeless youth. (January 2017) - Barman-Adhikari, Anamika; Al Tayyib, Alia; Begun, Stephanie; Bowen, Elizabeth; Rice, Eric
Abstract: Background: Nonmedical use of prescription drugs (NMUPD) among youth and young adults is being increasingly recognized as a significant public health problem. Homeless youth in particular are more likely to engage in NMUPD compared to housed youth. Studies suggest that network norms are strongly associated with a range of substance use behaviors. However, evidence regarding the association between network norms and NMUPD is scarce. We sought to understand whether social network norms of NMUPD are associated with engagement in NMUPD among homeless youth. Methods: 1046 homeless youth were recruited from three drop-in centers in Los Angeles, CA and were interviewed regarding their individual and social network characteristics. Multivariate logistic regression was employed to evaluate the significance of associations between social norms (descriptive and injunctive) and self-reported NMUPD. Results: Approximately 25% of youth reported past 30-day NMUPD. However, more youth (32.28%) of youth believed that their network members engage in NMUPD, perhaps suggesting some pluralistic ignorance bias. Both descriptive and injunctive norms were associated with self-reported NMUPD among homeless youth. However, these varied by network type, with presence of NMUPD engaged street-based and home-based peers (descriptive norm) increasing the likelihood of NMUPD, while objections from family-members (injunctive norm) decreasing that likelihood. Conclusions: Our findings suggest that, like other substance use behaviors, NMUPD is also influenced by youths' perceptions of the behaviors of their social network members. Therefore, prevention and interventions programs designed to influence NMUPD might benefit from taking a social network norms approach. Highlights: 23.61% of homeless youth (n = 1046) reported non-medical use of prescription drugs (NMUPD). Significant associations were found between perceived network norms (descriptive and injunctive) and NMUPD among this at-risk population. The associations between network norms and NMUPD varied by network type. Findings also indicate associations between other drug use (marijuana, heroin and injection drug use) and NMUPD. Interventions designed to target social network norms of NMUPD might be a viable strategy to reduce NMUPD among homeless youth.